2019
DOI: 10.4028/www.scientific.net/kem.821.81
|View full text |Cite
|
Sign up to set email alerts
|

A Nanoindentation Study on Al (TiFe-Mg-SiC) Composites Fabricated via Stir Casting

Abstract: The limitations of aluminium in most engineering applications has led to the development of aluminium matrix composites with improved microstructural and mechanical properties. Nanoindentation techniques was used in assessing the mechanical properties of fabricated aluminium matrix composites with ferrotitanium and silicon carbide as reinforcements. Results from nanoindentation experiments shows the dependence of modulus of elasticity, microhardness and contact depth on the dispersion of ferrotitanium and sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…A study on the microstructural and mechanical properties of stir-cast aluminum composite was carried out by Akinwamide et al (2020), in which SiC and FeTi were infused into the matrix at varying dosages of 2, and 5 wt.% saw improvement in the mechanical properties. In the same vein, Akinwamide et al (2019a, b) showed the role of ferrotitanium and silicon carbide on the properties in enhancing the properties of aluminium matrix.…”
Section: Introductionmentioning
confidence: 91%
“…A study on the microstructural and mechanical properties of stir-cast aluminum composite was carried out by Akinwamide et al (2020), in which SiC and FeTi were infused into the matrix at varying dosages of 2, and 5 wt.% saw improvement in the mechanical properties. In the same vein, Akinwamide et al (2019a, b) showed the role of ferrotitanium and silicon carbide on the properties in enhancing the properties of aluminium matrix.…”
Section: Introductionmentioning
confidence: 91%